Respon Siswa Terhadap Media Tangram dalam Memahami Konsep Bangun Datar Kelas VII - Tutus Zamania; Abdul Aziz; Wahyu Lestari (Program Studi Pendidikan Matematika, 2022)
This study aims to determine how students respond to tangram media in understanding the concept of flat shape. The method used in this research is quantitative descriptive method. The sample of this study was 5 students of class VII MTs Zainul Hasan in a limited scale trial and 33 students of class VII MTs Darut Tauhid in the main field trial. The results showed that on average all indicators of student response obtained a score of 84% with a very positive category. This means that the tangram media in understanding the broad concept of flat shapes gets a very positive response from students. Tangram media can be used during the learning process to improve students' abilities in understanding the broad concept of flat shapes and can improve other cognitive and affective aspects such as motivation, curiosity and student activity in learning.